Employer Brand of Choice: an employee perspective - Bellou, Victoria; Chaniotakis, Ioannis; Kehagias, Ioannis; Rigopoulou, Irini (Journal of Business Economics and Management, 2015)
This study seeks to contribute in the field of the ideal employer, by determining the Employer Brand of Choice and its core components. In doing so, a pilot study was initially conducted to delineate these components. Evidence from 896 working adults that participated in a field study support the multi-dimensionality of the construct Employer Brand of choice, highlighting the role of “Remuneration”, “Relationships”, “Opportunities for Self Development”, “Recognition”, and “Corporate Image”. These findings not only offer a concrete and holistic theoretical base of Employer Brand of Choice, but they can also serve as a managerial guide towards enhancing companies’ ability to attract, retain and motivate talented individuals.